English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve the inequality for x: 8x – 4 ≥ -4x + 32
x ≤ 7
x ≤ 3
x ≥ 7
x ≥ 3


7: Solve the inequality for x: (3/5)x ≤ 10 + (1/5)x
x ≤ 25
x ≤ 4
x ≥ 25
x ≥ 4


8: Solve the inequality for x: (3x – 2)/(4) > 4
x < 6
x < 2
x > 6
x > 2


9: Solve the inequality for x: 3(2 – 2x) > -4x + 8
x < -1
x < 1
x > -1
x > 1


10: Solve the inequality for x: (1/4)(3x + 2) ≤ (2/3)(-3 + 3x)
x ≤ 2
x ≤ (-13/3)
x ≥ 2
x ≥ (-13/3)


11: Look at the figures above. Select the appropriate inequality for Figure 1.
x < (-2/3)
x ≤ (-2/3)
x > (-2/3)
x ≥ (-2/3)

2007-02-15 02:31:06 · 6 answers · asked by me1026 1 in Science & Mathematics Mathematics

6 answers

when dealing with inequalities remember the following

1- > u can take a +ve no. to other side a -ve & perform operations like this as in the case of normal eqns

example:
a + b < c

a < b -c

2-> when multiplying both sides by a negative no. invert the inequality - repalce < by > & vice versa

example:

a < b
-a > - b


3-> when taking inverses on both sides invert the inequality

a < b

1/a > 1/b


use these rules & do the probelms urselves

2007-02-15 02:39:17 · answer #1 · answered by usp 2 · 0 0

x ≥ 3 it actually is x ≥ 2.6666666666667
x ≤ 25
x > 6
x > -1
x ≤ (-13/3)
x > (-2/3)

2007-02-15 02:51:39 · answer #2 · answered by s madhavan 1 · 0 0

8x - 4≥- 4x + 32

8x - 4 + 4x ≥ - 4x + 32 + 4x

12x - 4 ≥ 32

12x - 4 + 4 ≥32 + 4

12x ≥ 36

12x/12 ≥ 36/12

x ≥ 36/12

x ≥ 3

- - - - - - - -

3/5x ≤ 10 + (1/5)x

5(3/5)x ≤ 5(10) + 5(3/5)x

3x ≤ 50 + x

3x - x ≤ 50 + x - x

2x ≤ 50

2x/2 ≤ 50/2

x ≤ 50/2

x ≤ 25

- - - - - - -

3(2 - 2x) > - 4x + 8

6 - 6x > - 4x + 8

6 - 6x + 4x > - 4x + 8 + 4x

6 - 2x > 8

6 - 2x - 6 > 8 - 6

- 2x > 2

- 2x/-2 < 2 / -2

x < 2 / - 2

x < - 1

- - - - - - - -s-

2007-02-15 03:32:14 · answer #3 · answered by SAMUEL D 7 · 0 0

For increasing cubic binomials the final formulation is as follows: (a + b) ^ 3 = a^3 + 3*a^2*b^one million + 3*a^one million*b^2 + b^3 on your case, a is x and b is -y^5 So (x - y^5)^3 = x^3 + 3*x^2*(-y^5)^one million + 3*x^one million*(-y^5)^2 + (-y^5)^3 Simplified: =x^3 - 3x^2*y^5 + 3x*y^10 - y^15 :D

2016-12-17 16:49:58 · answer #4 · answered by Anonymous · 0 0

6.D 7.A 8.C 9.A 10.C 11.?

2007-02-15 02:43:37 · answer #5 · answered by Dulaamchik 1 · 0 1

u kno the time u spend
in typing these questions cud
actually be spent on solving them!
nobodys gonna come and
give ur exams for u

2007-02-15 02:36:05 · answer #6 · answered by Maths Rocks 4 · 0 1

fedest.com, questions and answers